IMPLEMENTASI PENDEKATAN DEEP LEARNING DALAM PEMBELAJARAN IPAS DI MADRASAH IBTIDAIYAH HABIBUL ABRORI LUMAJANG - Rohmatul Ummah (LPPM STAI Muhammadiyah Probolinggo, 2026)
The Deep Learning approach has recently gained attention as an educational innovation that promotes meaningful, mindful, and enjoyable learning experiences for students. Nevertheless, studies examining its application in Integrated Science and Social Studies (IPAS) instruction at Islamic elementary schools remain limited. This study sought to explore the implementation of the Deep Learning approach in IPAS learning at Madrasah Ibtidaiyah Habibul Abrori Lumajang, particularly in terms of lesson planning, instructional practices, assessment processes, and the factors that facilitate or hinder its implementation. A qualitative case study design was employed in this research. The participants included the school principal, an IPAS teacher, and students. Data were gathered through classroom observations, semi-structured interviews, and document analysis. The collected data were analyzed using the interactive model developed by Miles, Huberman, and Saldana, which consists of data condensation, data presentation, and conclusion verification. To ensure the trustworthiness of the findings, source triangulation and technique triangulation were applied. The results indicate that the implementation of the Deep Learning approach was reflected in the design of contextual learning plans, learner-centered instructional activities, and authentic assessment practices that emphasized both learning processes and outcomes. The principles of meaningful learning, mindful learning, and joyful learning were integrated into various learning activities, including observation, group discussion, reflection, and problem-solving tasks connected to students’ everyday experiences. Several factors supported the successful implementation of the approach, including teachers’ commitment to innovative instruction, support from the school administration, and students’ active participation. However, challenges were also identified, particularly limited instructional time and differences in teachers’ understanding of Deep Learning concepts and practices. Overall, the findings suggest that the Deep Learning approach can contribute to improving the quality of IPAS learning by creating more engaging, contextualized, and meaningful learning experiences for students.